Management of Preoperative Anxiety Patients with Progressive Muscle Relaxation Therapy Interventions - Indri Dwi Aristiani; Indri Heri Susanti (Inspirasi Foundation, 2022)
Objective: This case study aims to determine nursing care for anxiety in patients with pre-operative kidney stones (ureteroscopy) with progressive muscle relaxation therapy intervention in the Wijaya Kusuma room below the Kardinah Hospital, Tegal City. Method: The method used is a descriptive case study design where the case study sample is pre-operative kidney stone patients. The instrument used was the DASS 42 questionnaire (Depression Anxiety Stress Scale 42). Result: The results of the case study on the third day showed the patient looked calm with vital signs blood pressure 120/70 mmHg, pulse 97x/minute, RR 21x/minute, temperature 36.1°C, a decrease in the results of the DASS questionnaire from before the action 18 to 11. Conclusion: The results of the case study showed a decrease in anxiety in patients with preoperative kidney stones.